2013
DOI: 10.4161/cc.25452
|View full text |Cite
|
Sign up to set email alerts
|

Complex mutual regulation of facilitates chromatin transcription (FACT) subunits on both mRNA and protein levels in human cells

Abstract: rePortFacilitates chromatin transcription (FaCt) is a chromatin remodeling complex with two subunits: SSrP1 and SPt16. Mechanisms controlling FaCt levels are of interest, since the complex is not expressed in most differentiated cells, but is frequently upregulated in cancer, particularly in poorly differentiated, aggressive tumors. Moreover, inhibition of FaCt expression or function in tumor cells interferes with their survival. Here we demonstrate that SSrP1 and SPt16 protein levels decline upon induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 28 publications
(46 reference statements)
13
61
0
Order By: Relevance
“…2F). Since a parallel study demonstrated co-regulation of SSRP1 and SPT16 levels, shRNA against either FACT subunit effectively eliminated both SSRP1 and SPT16 (Safina et al, 2013). We found that FACT KD suppressed growth of all tumor cells, but had a smaller or no effect on growth of non-transformed cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2F). Since a parallel study demonstrated co-regulation of SSRP1 and SPT16 levels, shRNA against either FACT subunit effectively eliminated both SSRP1 and SPT16 (Safina et al, 2013). We found that FACT KD suppressed growth of all tumor cells, but had a smaller or no effect on growth of non-transformed cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1B and C). This is most likely due to the demonstrated dependence of SPT16 protein levels on SSRP1 (Safina et al, 2013). Nevertheless, as for SSRP1 mRNA, a significant number of tumors with very high levels of SPT16 mRNA were observed among various types of cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of SSRP1 mRNA, both protein components are depleted. Similarly, when SSRP1 mRNA is overexpressed, Spt16 protein levels also increase (38).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the effect of the FACT complex on ALV integration in infected cells, we employed a chicken cell line (DT40) with various levels of expression of the FACT complex. Previous research has shown that the expression and abundance of the FACT complex are regulated by a complex feedback loop in which SSRP1 mRNA plays a critical role (38). The presence of SSRP1 mRNA is essential for the stability of the Spt16 protein and the FACT complex as a whole.…”
Section: Resultsmentioning
confidence: 99%